Remote Academic Platforms in Times of a Pandemic - Nathalia Ospina García (Kassel University Press, 2021)
The pandemic has accelerated the use and development of video conferenc-ing platforms due to COVID-19, and it is necessary to find an application that best suits our requirements. This article evaluates nine features of nine video conferencing applications to find the best choice. A detailed analysis has been conducted in this article using surveys to collect data from two samples at national and international level. The methodology followed is the CDIO methodology, a tool to address complex problems in four stages: conception, design, implementation, and operation. The primary aim of this paper is to examine which is the best livestreaming option according to the selected criteria, using, as references, well-known applications such as Jitsi, Zoom, Microsoft Teams, Google Meet, Big Blue Button, among others. An application of multicriteria analysis is also shown to support the evalua-tion of these platforms compared to the established criteria.